Coaching adaptive skill and expertise in Premier League football academies-paving a way forward for research and practice - Michael Ashford; Michael Ashford; Jamie Taylor; Jamie Taylor; Danny Newcombe; Áine MacNamara; Stephen Behan; Stephen Behan; Simon Phelan; Simon Phelan; Scott McNeill (Frontiers Media S.A., 2024)
Within the domain of coach education researchers have long called for a paradigm shift, whereby the quality of coaching practice is no longer measured against a checklist of prescribed competencies. This desire to evolve coach education and development, has been aligned to the need to better identify, understand and utilise what adaptive skill and expertise looks, sounds and feels like across specific sport coaching contexts. This paper outlines a broader research plan for the Premier League to drive the progress of research informed practice, in turn shaping a coach development agenda focused on developing adaptive and skilful coaches within Academies. In turn, this is a core feature of the Premier Leagues institutional aim of developing the most skilful coaches in the world. However, in order to begin the process of initiating such a shift in the way things work, there is a need to seek first to understand, before being understood. Therefore, to demonstrate an evidence informed basis to this shift within coach education and development, we ask three questions; (1) Do we understand what the coaches with the highest level of expertise can do? (2) How should we identify coaches with expertise across different contexts? (3) What does coaching expertise research need to do? In answer to these questions, we present the lack of empirical investigation previously conducted in the sports coaching discipline to explore coaching expertise and draw on wider domains to offer possible capacities of skilful coaches who possess expertise. To identify coaches with expertise, coherent with the broader expertise literature, we suggest that this is best conducted via means of social validation. Finally, we offer a road map of investigation designed to explore expertise, formed of a mix of evidence informed methodologies which have not yet been utilised in sport coaching research.